1996
DOI: 10.1177/000331979604700602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Coagulation and Fibrinolytic Systems in Men with Intermittent Claudication

Abstract: The authors evaluated elements of the coagulation and fibrinolytic systems in 18 male patients with intermittent claudication vs 19 men matched for risk factors who served as controls. Prothrombin time and activated partial thromboplastin time did not significantly differ in the patients and the controls. The plasminogen level in the two groups was not significantly different. The level of lipoprotein(a) was significantly higher in the patients than in the controls. The levels of antigen and the activity of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Many studies have suggested that patients with PAD manifest platelet hyperaggregability, increased levels of soluble platelet activation markers, enhanced thrombin generation and altered fibrinolytic potential (summarised in table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These findings, which are consistent across the different stages of PAD, have important ramifications. Individually, many of the markers characterising the prothrombotic environment of PAD are predictive of future cardiovascular events.…”
Section: Pad and Thrombogenesismentioning
confidence: 81%
See 1 more Smart Citation
“…Many studies have suggested that patients with PAD manifest platelet hyperaggregability, increased levels of soluble platelet activation markers, enhanced thrombin generation and altered fibrinolytic potential (summarised in table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These findings, which are consistent across the different stages of PAD, have important ramifications. Individually, many of the markers characterising the prothrombotic environment of PAD are predictive of future cardiovascular events.…”
Section: Pad and Thrombogenesismentioning
confidence: 81%
“…Higher TM levels Cortellaro 11 50 PAD/58 CAD or CVD controls without PAD Higher D-dimer and lower tPA antigen and fibrinolytic capacity; D-dimer and fibrinolytic capacity predictive of subsequent vascular events Devine 12 29 PAD/10 controls Higher anti-factor XIII a-chain binding to platelets Gosk-Bierska 13 59 PAD/26 controls Higher vWF, fibrinogen, TAT and PF4 Gresele 14 63 PAD/18 controls Higher urinary 11-dehydro-thromboxane B2 levels Handa 15 18 PAD/19 controls Higher TM, fibrinogen, a1-AT and TAT; lower a2-PI levels Killewich 16 69 PAD/11 controls Higher PAI-1 and tPA antigen; lower tPA activity Koksch 17 50 PAD/50 controls Higher fibrinogen, vWF, PAI-1, tPA, P-selectin on both stimulated and non-stimulated platelets; lower PAI-1/tPA ratio Lowe 18 388 PAD/1581 controls Higher blood viscosity, hematocrit, fibrinogen, leucocyte elastase, and uric acid; haematocrit and viscosity directly correlated with PAD severity Makin 19 234 PAD/50 controls Higher soluble P-selectin, vWF, TF and fibrinogen; fibrinogen directly correlated with PAD severity McDermott 20 346 PAD/203 controls D-dimer and hsCRP inversely correlated with limb function in both PAD and controls Reininger 21 92 PAD/70 controls Higher platelet adhesion and aggregation, fibrinogen, fibrin monomer, d-dimer and TAT Robless 22 20 PAD/20 controls Higher spontaneous and induced platelet aggregation Zeiger 23 50 PAD/50 controls Higher P-selectin expression on platelets, platelet aggregates and platelet-derived microparticles a1-AT, a 1-antitrypsin; a2-PI, a 2-plasmin inhibitor; CAD, cardiovascular disease; CVD, cerebrovascular disease; hsCRP, highly sensitive C reactive protein; PAI-1, plasminogen activator inhibitor 1; PF4, platelet factor 4; TAT, thrombin-antithrombin complex; TM, thrombomodulin; tPA, tissue plasminogen activator; vWF, von Willebrand Factor. Overall 9% reduction favouring clopidogrel (p = 0.043); 24% reduction in PAD subgroup (p = 0.003) CHARISMA 33 Clopidogrel + ASA v ASA 15 603 with atherosclerosis including 2838 with PAD Overall 7% reduction favouring clopidogrel (p = 0.22); 13% reduction in PAD subgroup (p = 0.29) CREDO 34 Clopidogrel + ASA v ASA 2116 patients including 272 with PAD or CVD Overall 27% reduction favouring clopidogrel (p = 0.02); 48% reduction in PAD/CVD subgroup (p = 0.06) EMATAP 35 Ticlopidine v placebo 615 patients with claudication 74% reduction favouring ticlodipine (p = 0.002) STIMS 36 Ticlopidine v placebo 687 patients with claudication Non-significant 11% reduction favouring ticlopidine (p = 0.24); 29% reduction in all-cause mortality (p = 0.015) Thromboxane inhibitors ADEP 37 Picotamide v placebo 2304 patients with claudication Non-significant 19% reduction favouring picotamide (p = 0.056) DAVID …”
Section: Pad/40 Controlsmentioning
confidence: 99%
“…55,56 enhanced levels of fibrinogen, alpha-1-antitrypsin, thrombin/antithrombin iii complex, alpha-2 plasmin inhibitor/plasmin complex, and thrombomodulin were documented in claudicants. 57 Compared with healthy control subjects, patients with critical limb ischemia show higher t-Pa antigen, Pai-1 antigen, and d-dimer levels both at rest and after exercise. thrombin formation is enhanced in these patients after submaximal treadmill exercise.…”
Section: Risk Factorsmentioning
confidence: 96%
“…higher d-dimer levels are associated with poorer functional activity measures, 33 however, the significance of such findings is unknown. 57,58…”
Section: Risk Factorsmentioning
confidence: 99%
“…Patients with established PAD have a higher level of circulating tissue factor, exaggerated thrombin production, and further reduced fibrinolytic potential when compared to healthy individuals, and this is consistent with possible underlying prothrombin status. 48,49 There are two major types of anti-coagulants that are currently involved in managing patients with PAD. The first are vitamin K epoxide reductase inhibitors, namely Warfarin, and the second are directly acting oral anticoagulant agents (DOAC).…”
Section: Role Of Anti-coagulation Therapy In Pad Patientsmentioning
confidence: 99%